Perkembangan Pendidikan Anak-Anak Tionghoa Pada Abad 19 Hingga Akhir Orde Baru Di Indonesia - Noor Isnaeni - ABA BSI (Universitas Bina Sarana Informatika, 2012)
ABSTRACT - In the 19th century the Dutch East Indies government did not care about education for Chinese children. When the clothing, food and shelter were fulfilled, Chinese people began to think about their children's education. Finally, Chinese people made an association named THHK (Tiong Hoa Hwee Koan) on March 17, 1900. The purpose of this scientific writing is to find out how the development of the educational of Chinese children in the 19th century until the collapse of new era and what the Chinese people doing for the education of their children at that time. The research method used is the method of historical research, that is: heuristics, source criticism, interpretation and historiography. The main purpose of the establishment of schools THHK is to spread the religion of Confucius. By coming out Chinese schools established by the Chinese people, it caused that the Dutch East Indies government worried of the Chinese people and their offspring’s nationalism growing up. Therefore, the Dutch East Indies government found Holandsch Chineesche School (HCS) – it was built up for Chinese people with Dutch language as the main language.Key Words: development, education, childrens of chinese, in Indonesia.